Dylematy oceny sprawności funkcjonowania rynków rolnych - Zieliński, Kazimierz (Dilemmas of Evaluating the Effectiveness of Agricultural Markets Functioning, 2005)
After presenting the free market concepts for agriculture, the study deals with possible large corporations and government control of market as well as with criteria of evaluation of market functioning. The later part of the paper is devoted to establishing a procedure which serves to evaluate the ability of the policy to move the exchange system closer to or further away from each of the goals implied by the criteria.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 460-465